1978
DOI: 10.1159/000232103
|View full text |Cite
|
Sign up to set email alerts
|

Histamine in Nasal Secretions

Abstract: The histamine content of secretions collected by small-volume nasal washes was assayed by a spectrophotofluorometric method. A wide range of histamine concentrations (< 5–1, 519 ng/ml) was found. The mean concentration in secretions from normal individuals (91 ng/ml) was not significantly different from that found in allergic individuals (51 ng/ml). Females had significantly lower concentrations than did males. Sequential sampling in normals and allergies showed a great deal of daily variation in histamine con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
9
0

Year Published

1982
1982
2000
2000

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(10 citation statements)
references
References 16 publications
1
9
0
Order By: Relevance
“…Prior to provocation, five lavages were performed at 4-rain intervals. As previously observed by us (Miadonna et al 1987) and others (Eggleston et al 1978), high histamine levels can be detected in the first nasal lavages from some symptomfree subjects who have not been exposed to allergens. Therefore, five preliminary lavages were performed to obtain low and uniform prechallenge mediator levels.…”
Section: Nasal Stimulation Nasal Lavage Procedures and Symptom Registsupporting
confidence: 79%
“…Prior to provocation, five lavages were performed at 4-rain intervals. As previously observed by us (Miadonna et al 1987) and others (Eggleston et al 1978), high histamine levels can be detected in the first nasal lavages from some symptomfree subjects who have not been exposed to allergens. Therefore, five preliminary lavages were performed to obtain low and uniform prechallenge mediator levels.…”
Section: Nasal Stimulation Nasal Lavage Procedures and Symptom Registsupporting
confidence: 79%
“…Eggleston et al [1978] found histamine concentrations in nasal secre tions ranging from 0 to 1,419 ng/ml (mean 91 ng/ml), and were also able to show that the concentration of histamine varies widely from day to day in the same subject, and that essentially there was no difference between normal and atopic individuals. Thus it ap pears that normal nasal mucosa produces some free histamine.…”
Section: Discussionmentioning
confidence: 77%
“…The rationale for several baseline lavages is to decrease the levels of mediators before challenge in order to detect the changes in mediator concentrations induced by the challenge more efficiently. It is well known that there is a significant concentration of histamine in the nose at rest, even in healthy subjects [37]. However, we were interested in other substances, such as substance P and tryptase, the concentrations of which are known to be low in nasal lavage fluid [10,38].…”
Section: Discussionmentioning
confidence: 99%